Rural radio and the everyday politics of settlement on Indigenous land. (September 2020) - Waller, Lisa; Mesikämmen, Emma; Burkett, Brian
The Australian Broadcasting Corporation's Country Hour radio programmes are produced regionally and promote specific understandings of rurality. This article presents an analysis that shows Indigenous people and issues are rarely sources or topics in Country Hour, and that stories about Indigenous land use are generally broadcast only if the land is used in a way that is seen as 'productive' through settler colonial eyes. It also argues the programme should include Indigenous voices and understandings of the land in imagining this space. It makes a theoretical contribution to media studies by extending on concepts of the 'rural imaginary' and 'settler common sense' to argue that the programme perpetuates a discourse that legitimates and valorises the use of 'rural' space for non-Indigenous people, concepts and activities. Indigenous people are noticeably absent and silent. Country Hour is therefore conceptualised as a media space that continues to transmit settler colonialism and its attendant myths.